Os efeitos dos intangíveis nas previsões dos analistas financeiros - Gazoni Junior, Gilmar Gomes (2017)
This study investigates the relationship between intangibles and financial analysts’ forecasts and was motivated by the suggestion on literature, that intangibles can influence analysts' predictions, even though there is no consensus as to the direction of such influence. In this way, we tried to contribute by adding to the discussion evidence through other approaches adding the use of another proxy (Goodwill) of intangible and also the segregation of companies by the degree of intangibility and thus, observing the behavior for each intangible studied as well as the same proxy when to a greater or lesser degree. The general objective is to investigate the relationship between intangible assets and forecasts of financial analysts and specifically to analyze whether intangible assets influence the accuracy and dispersion of forecasts. To achieve the research objectives was used a sample of US nonfinancial firms from 1995 to 2016, and the main results found evidences that investments in R&D and recognized intangible assets are capable of improving analysts' forecasts. However, Goodwill was negatively related to analysts' forecasts by reducing accuracy and increasing the dispersion forecasts. In addition, when analyzed by the degree of intangibility, companies with a lower degree of R&D investment showed a reduction in accuracy and an increase in the dispersion of forecasts, while companies with a higher degree of investment in R&D showed an increase in accuracy and a reduction in the dispersion of forecasts. Thus, it was evidenced that there is an association between intangibles and predictions, but it is emphasized that the sign of this association depends on the intangible in question and also degree of intangibility.